Maize Seed Germination Under Low-Temperature Stress Impacts Seedling Growth Under Normal Temperature by Modulating Photosynthesis and Antioxidant Metabolism - Meng, Aiju; Wen, Daxing; Zhang, Chunqing (Frontiers in Plant Science, 2022)
Spring maize is usually subjected to low-temperature stress during seed germination, which retards seedling growth later even under a suitable temperature. However, the mechanism underlying maize seed germination under low-temperature stress impacting seedling growth is still ambiguous. In this study, we used one low-temperature sensitive maize (SM) and one low-temperature resistance maize (RM) to investigate the mechanism. The results showed that the SM line had higher lipid peroxidation (malondialdehyde [MDA]) and lower total antioxidant capacity and germination percentage than the RM line under low-temperature stress, indicating the vulnerability of SM line to low-temperature stress. Further transcriptome analysis revealed that seed germination under low-temperature stress caused the down-regulation of photosynthesis-related gene ontology (GO) terms in two lines. Moreover, the SM line displayed down-regulation of ribosome and superoxide dismutase (SOD) related genes, whereas genes involved in SOD and vitamin B6 were up-regulated in the RM line. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis revealed that photosynthesis and antioxidant metabolism-related pathways played essential roles in response to low-temperature stress during seed germination. The photosynthetic system displayed a higher degree of damage in the SM line. Both qRT-PCR and physiological characteristics experiments showed similar results with transcriptome data. Taken together, we propose a model for maize seed germination in response to low-temperature stress.